(untitled) - Byham, William C. (New York, 1993)
For the nearly one million Americans who work for Japanese companies in North America, this truly helpful guide shows the best way to success. Based on extensive research and experience, this book is co-written by the author of Zapp!, which sold more than 1,000,000 copiees
Keywords: Quản trị sản xuất công nghiệp,Industrial management,Industrial management,Corporations, Japanese,Tổng công ty, Người Nhật,Quản trị sản xuất công nghiệp; Nhật Bản,Japan,North America,North America,Bắc Phi,Bắc Phi